The Effect of Brand Feelings on Perceived Destination Image (International Journal of Financial, Administrative and Economic Sciences, 2025)
The objective of this study was to offer an integrated approach to understanding brand feelings by examining the theoretical and empirical evidence on the causal relationships among the components of brand feelings dimensions and overall perceived destination image of Feynan Ecolodge. A research model was proposed in which sex hypotheses were developed. The empirical data was collected in a major tourism destination in Feynan site. A total of 42 questionnaires were returned and the data were analyzed using a series of multiple regressions to determine the relationship between brand feelings dimensions and brand image. The results supported the proposed model: (1) warmth, fun, excitement, security, social approval and self-respect directly influenced brand image; (2) there is a significant impact of the brand feelings dimensions on perceived image of Feynan Ecolodge. The theoretical and managerial implications were drawn based on the study finings, and recommendations for future researchers were made, and limitations and conclusions are discussed.
Keywords: Brand Feelings Dimensions; Perceived Brand Image; Feynan Ecolodge